Influence of the mother’s endocrine pathology on the formation of the fetal internal organs - V. D. Markowski; L. S. Kupriyanova (Zaporožskij Medicinskij Žurnal)
Aim. Results of comprehensive study of the morphological structure of the female genital organs of dead fetuses from the mothers with pregnancy complications showed structure abnormalities of the fetus.